Screening and Assessment of Nutritional Status on Elderly in Pampang, Makassar - Darmiaty Darmiaty; Nuurhidayat Jafar; Silvia Malasari (Indonesian Contemporary Nursing Journal, 2017)
Background: Aging is a condition or individual circumstances which unavoidable. One of the attempts to achieve optimal health status is by improving the nutritional need of the society, especially the elderly.The increasing of elderly number will cause various complex problems for elderly families and society.The purpose of this research is to figure out the overview of screening and assessment of nutritional status in elderly at Pampang village in Makassar. Methods: Quantitative research with descriptive research design is used as a method of this research. Samples were obtained by using consecutive sampling with a total sample 152 eligible respondents. Results:The screening results of the first phase showed 38.2% of the elderly have a normal nutritional status, 50% of the elderly are at risk of malnutrition, and 11.8% of the elderly have a malnourished nutritional status.The results of the phase II assessment which were obtained from  94 respondents from the first phase (malnutrition respondent and respondent having risk of malnutrition) showed 7.4% of them have a normal nutritional status, 78.7% are at risk of malnutrition, and 13.8%  have a malnourished nutritional status. Conclusion: Based on the results of phase II, it is showed that more than two third of respondents (78.7%) are at risk of malnutrition. The assessment of nutritional status should be conducted every 3 months in the elderly in order to prevent the risk of malnutrition and the malnutrition it self.